Etnokonservasi Mata Air Pada Ritual Mandi Suci dan Nimba Banyu di Sendang Tirto Kamandanu Kabupaten Kediri - Abrilliant, Putri Salma; Sulistiyowati, Tutut Indah; Sulistiono, Sulistiono (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2025)
Wellhead has a vital role for humans. Conservation efforts are key to maintaining springs. However, local wisdom-based conservation, particularly cultural practices, has received more attention than science-based conservation. This study aims to determine the cultural ritual practices at Sendang Tirto Kamandanu and their role in conservation. The study was conducted from November 2024 to April 2025 using a qualitative approach with ethnographic methods in Menang, Pagu, Kediri. The data consisted of recordings and photographs obtained through interviews using the snowball sampling technique, involving the head of the cultural and nature conservation division of the Kediri Regency Tourism Office, the head of the Village Consultative Body (BPD) of Menang Village, the site caretaker (juru kunci), and visitors. The data were then compared across respondents to identify similarities, differences, and emerging findings within the studied population. Finally, conclusions were drawn and presented in a narrative form. The results revealed five ethnoconservation practices at Sendang Tirto Kamandanu: ritual mandi suci, nimba banyu, pengkain kuning, sesrawung ringin sanga, and 1 suro. Through these cultural ritual practices, Sendang Tirto Kamandanu has been well maintained and conserved to date. This research is expected to enrich ethnoconservation studies in environmental conservation education, especially at Nusantara PGRI Kediri University.